2018
DOI: 10.3390/s18092855
|View full text |Cite
|
Sign up to set email alerts
|

Features of Invariant Extended Kalman Filter Applied to Unmanned Aerial Vehicle Navigation

Abstract: This research used an invariant extended Kalman filter (IEKF) for the navigation of an unmanned aerial vehicle (UAV), and compared the properties and performance of this IEKF with those of an open-source navigation method based on an extended Kalman filter (EKF). The IEKF is a fairly new variant of the EKF, and its properties have been verified theoretically and through simulations and experiments. This study investigated its performance using a practical implementation and examined its distinctive features co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…with F χ e (χ χ χ e , U) = ∂ F (χ χ χ e , U) ∂ χ χ χ e χ χ χ e ,U ∈ IR 18×18 (33) computed by the same procedure used to define Z. Notice that χ χ χ e =χ χ χ e (t) and U = U (t).…”
Section: Uncertainties Estimation Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…with F χ e (χ χ χ e , U) = ∂ F (χ χ χ e , U) ∂ χ χ χ e χ χ χ e ,U ∈ IR 18×18 (33) computed by the same procedure used to define Z. Notice that χ χ χ e =χ χ χ e (t) and U = U (t).…”
Section: Uncertainties Estimation Algorithmmentioning
confidence: 99%
“…Wind effects are estimated by observers, stochastic or deterministic as ( [24], while [25] presents an estimation strategy to compensate the external wrench exerted on the aerial multi-link robot while estimating external forces. Different state-estimation techniques as sliding-mode based observers [26] are also used to improve the performance of the system, however, due to its performance the Kalman Filter is widely used [27], [28], [29], [30], [31], [32], [33], [34], [35]. In this paper, we consider a multi-link aerial system that is intended to track a time-based trajectory while rejecting parametric and external disturbances during a multiple-load transportation task.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, data processing with appropriate filters can stabilize the measurement signals from an IMU. Kalman (15)(16)(17)(18) and complementary filters (19)(20)(21)(22)(23) are two widely used filters. In a previous work, (24) an experimental comparison of both filters found that they can obtain smooth and accurate signals regardless of dynamic or static experiments.…”
Section: Complementary Filtermentioning
confidence: 99%
“…It was indicated that adaptive Kalman filtering can improve the accuracy of vehicle LDV. Ko et al [8] used an invariant extended Kalman filter for the navigation of an unmanned aerial vehicle. Tradacete et al [9] presented a global positioning system for an autonomous electric vehicle.…”
Section: Introductionmentioning
confidence: 99%